Identifying a test to monitor weightlifting performance in competitive male and female weightlifters - Travis, S. K.; Goodin, J. R.; Beckham, G. K.; Bazyler, C. D. (Sports, 2018)
Monitoring tests are commonly used to assess weightlifter`s preparedness for competition. Although various monitoring tests have been used, it is not clear which test is the strongest indicator of weightlifting performance. Therefore, the purpose of this study was to (1) determine the relationships between vertical jump, isometric mid-thigh pull (IMTP) and weightlifting performance; and (2) compare vertical jumps to IMTP as monitoring tests of weightlifting performance in a large cohort of male and female weightlifters. Methods: Fifty-two competitive weightlifters (31 males, 21 females) participated in squat and countermovement jump testing (SJ, CMJ), and IMTP testing performed on force plates. All laboratory testing data was correlated to a recent competition where the athletes had attempted to peak. Results: Squat jump height (SJH) was the strongest correlate for men and women with the Sinclair Total (r = 0.686, p = 0.01; r = 0.487, p = 0.05, respectively) compared to countermovement jump height (r = 0.642, p = 0.01; r = 0.413, p = 0.063), IMTP peak force allometrically scaled to body mass (r = 0.542, p = 0.01; r = -0.044, p = 0.851) and rate of force development at 200 ms (r = 0.066, p = 0.723; r = 0.086, p = 0.711), respectively. Further, SJH was a stronger correlate of relative weightlifting performance compared to IMTP peak force in females (p = 0.042), but not male weightlifters (p = 0.191). Conclusions: Although CMJ and IMTP are still considered strong indicators of weightlifting performance, SJH appears to be the most indicative measure of weightlifting performance across a wide-range of performance levels. Thus, SJH can be used as a reliable measure to monitor weightlifting performance in male and female weightlifters.